Comparative Efficacy of Cypermethrin - Creosote and CCA-Creosote Treatments against Biodeterioration of Rubber Wood under Field Conditions - Edwin, Leela (Fishery Technology, 2025)
Synthetic pyrethroids are increasingly being used as wood preservatives because of theirhigh degree of contact toxicity, low solubility and low mammalian toxicity. A mixture ofcypermethrin, a synthetic pyrethroid, with creosote is tried for its efficacy againstbiodeterioration of rubber wood under marine, atmospheric and soil conditions. This has beencompared with the performance of CCA-creosote treatment, which has been effectively usedfor increasing the durability of many non-durable timbers. The compressive stress parallelto grain of the untreated, treated and exposed panels is assessed. The creosote componentimparts higher strength to the treated wood in both types of treatments. It is seen that thecypermethrin- creosote mixture imparts resistance to biodeterioration under atmospheric andsoil conditions while dual treatment with Copper-Chrome -Arsenic (CCA) and creosote ismore effective under marine conditions.